Content reading and literacy / succeeding in today's diverse classrooms. - Alvermann, Donna E.; Phelps, Stephen F. (Boston : Allyn and Bacon, 1998)
One of the only content area books with a strong focus on diversity. Strongly grounded in research with strategies and lesson and unit planning exercises. Discusses reading literature content areas with extensive lists of trade literature in appendices.
Includes bibliographical references and indexes.
Keywords: Content area reading; Reading (Secondary); Multicultural education; Reading (Secondary); Teenagers